Exosomes combined with extra virgin olive oil reduces lipogenesis, oxidative stress, and inflammation in non-alcoholic fatty liver disease model - Bassam F. Alowaiesh; Doaa Ibrahim; Ayman A. Saleh; Haifa A. S. Alhaithloul; Abdulsalam A. M. Alkhaldi; Ahmed Abdelfattah-Hassan (PLoS ONE, 2025)
In response to high-fat-diet, excessive lipid accumulation in the liver results in chronic damage and inflammation. Olive oil has been studied for its health beneficial effects in hyperlipidemia (mainly has lipids lowering and antioxidative potential) while mesenchymal stem cells derived exosomes (MSCs-Exo) are investigated mainly for their tissue regenerative and anti-inflammatory potential. In the present study we aimed to combine the beneficial effects of Extra Virgin Olive Oil (EVOO) and MSCs-Exo on a model of high-fat-diet induced Non-Alcoholic Fatty Liver Disease (NAFLD, which still lacks effective treatment protocols) and detect whether an improved response could be achieved from this combination. Sprague Dawley rats (n = 40) were randomly assigned to five groups (n = 8/group), control, hyperlipidemia (HL), HL+EVOO, HL + Exo and HL + Exo+EVOO. Our results show that better antihyperlipidemic effects were obtained in the combined group receiving Exo+EVOO treatment more than using EVOO or MSCs-Exo alone. This was achieved by improving plasma lipids profile, improving antioxidants stores and reducing lipid peroxidation, no change in liver function parameters which was confirmed also by the histopathological examination of the liver where a preserved normal liver architecture. To further elucidate the mechanisms involved, the gene expression levels of lipogenesis (SREBP-1c, ACC, FAS, GPAT3, SCD1, and FSP27), inflammation (IL-1β, TNF-α, IL-6, IL-18, CCL20, and NF-κB), lipid peroxidation (CPT1A, ACOX1) and PPAR pathway (PPARα, PPARγ) were all normalized. This indicates that combined Exo+EVOO harnessed the benefits of both, and this was much better in treating hyperlipidemia and NAFLD and warrants prospects for approaches that could be adopted to treat NAFLD.